Clinical epidemiology : the essentials - Fletcher, Grant S (Wolters Kluwer, 2021)
The publication focuses on the basics of clinical epidemiology and evidence-based medicine. Intended for professionals.
International edition
Keywords: Epidemiologic Factors; Epidemiologic Methods; klinické lékařství; epidemiologické faktory; Clinical Medicine; Evidence-Based Medicine; epidemiologické metody; medicína založená na důkazech; epidemiologie